2020
DOI: 10.3390/molecules25184194
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection of an ATP-Binding TNA Aptamer

Abstract: Recent advances in polymerase engineering have made it possible to isolate aptamers from libraries of synthetic genetic polymers (XNAs) with backbone structures that are distinct from those found in nature. However, nearly all of the XNA aptamers produced thus far have been generated against protein targets, raising significant questions about the ability of XNA aptamers to recognize small molecule targets. Here, we report the evolution of an ATP-binding aptamer composed entirely of α-L-threose nucleic acid (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…24) against both protein 139, 487-489 and small molecule targets. 490,491 Evolved polymerases also facilitate the selection of aptamers with other sugar modifications such as 2′-OMe groups 492 or bulkier functionalities appended at the 2′-position of the ribose. 493 In the latter approach, an engineered polymerase capable of efficient polymerization of 2′-modified nucleotides was used to construct libraries containing 2′-N 3 -modified cytosine nucleotides.…”
Section: Sugar-modified and Xna Containing Aptamersmentioning
confidence: 99%
“…24) against both protein 139, 487-489 and small molecule targets. 490,491 Evolved polymerases also facilitate the selection of aptamers with other sugar modifications such as 2′-OMe groups 492 or bulkier functionalities appended at the 2′-position of the ribose. 493 In the latter approach, an engineered polymerase capable of efficient polymerization of 2′-modified nucleotides was used to construct libraries containing 2′-N 3 -modified cytosine nucleotides.…”
Section: Sugar-modified and Xna Containing Aptamersmentioning
confidence: 99%
“…The work demonstrated that TNA could fold into tertiary structures with retained chemical functions, suggesting TNA as an RNA progenitor in the pre-RNA world. After that, various TNA aptamers with the capability of binding to small molecules and large proteins have been selected [ 178 , 179 , 180 , 181 , 182 , 183 ]. These TNA aptamers have remarkable thermal and biological stability.…”
Section: Chemically Modified Nucleic Acid Analoguesmentioning
confidence: 99%
“…This demonstrates the remarkable biostability of the TNA aptamer and the high level of selectivity in a large background of competing biomolecules. More recently, an ATP-binding aptamer composed entirely of TNA was obtained which showed high affinity to ATP and strong specificity against other naturally occurring ribonucleotide triphosphates [105]. TNA aptamer sequence can be minimized to a length that is compatible with chemical synthesis, which enables new applications that were previously not feasible for XNA aptamers due to the limited practical scale of enzymatic synthesis [104].…”
Section: Xeno-nucleic Acidsmentioning
confidence: 99%